Maintenance Therapy with Trastuzumab in Her2 Positive Metastatic Parotid Ductal Adenocarcinoma - Muhammad Shahid Iqbal; Ghazia Shaikh; Sanjoy Chatterjee; Helen Cocks; Josef Kovarik (Case Reports in Oncological Medicine)
Salivary ductal carcinomas (SDCs) are extremely rare and aggressive malignancies, accounting for approximately 6% of all salivary gland malignancies. One distinct feature is their resemblance to ductal carcinomas of breast. A significant percentage of SDCs overexpress Her2 and the use of targeted therapy with trastuzumab can be considered in these patients. We report a rare case of long term disease control with trastuzumab in Her2 positive metastatic parotid ductal carcinoma. Our case also highlights that isolated brain metastasis should be managed aggressively to allow optimal local control when systemic disease is under remission with trastuzumab. We have also reviewed the published literature on the use of trastuzumab in SDCs.